Формування гiдрогелiв, прищеплених до полiмерної поверхнi для бiомедичних застосувань - Тарнавчик, I.Т.; Самарик, В.Я.; Воронов, А.С.; Варваренко, С.М.; Носова, Н. Г.; Когут, А.М.; Воронов, С.А. (Видавничий дім "Академперіодика" НАН України, 2008)
A method to improve the mechanical properties of hydrogels by grafting them to a peroxidized polypropylene surface has been developed. It is shown that the grafting occurs due to the peroxidation of the polymer surface via the preliminary grafting of heterofunctional peroxide macromolecules and water soluble polymer chains to it.